Assessment of groundwater quality properties in a university sub-urban community in Delta State, Nigeria: part b-correlation analysis and household water treatment adoption - H.I. Owamah (Journal of Applied Sciences and Environmental Management, 2019)
In this paper, the correlation analysis of the physical and chemical properties of bore-holes (BHs) and hand-dug wells (HDWs) water samples monitored in Oleh, Delta State, is reported. Households were also interviewed to evaluate level of access to clean water, quality of water and knowledge of water treatment. The correlation analysis showed that the major cations and anions contributing to TDS are Na (0.92), Mg (0.85), Ca (0.83), K (0.77), and SO42- (0.89) and Cl- (0.88) respectively. Chloride ion (Cl−) was also found to be linked to Na-Mg group with perfect correlations (0.92-0.90). While Pb and Cd had very strong correlations with the anions, SO42– also correlated well with Ba, Na, K and Mg. Total coliform bacteria was found higher in HDWs indicating that boreholes in the community were safer sources drinking water. About (<32%) of the households surveyed accessed water from HDWs and never practiced any form of household water treatment. Majority of the HDW water samples (72%) fell within the class of “low risk (FC, >11-100cfu/100 mL). The study recommends regular monitoring of study area groundwater and the provision pipeborne water.